CARE: an observational study of adherence to home nebulizer therapy among children with asthma. (February 2021) - Zhao, Deyu; Chen, Dehui; Li, Ling; Zou, YingXue; Shang, Yunxiao; Zhang, Chonglin; Zhang, Li; Pan, Jiahua; Chen, Qiang; Ai, Tao; Ni, Qian
Background: The prevalence of pediatric asthma in China is approximately 3%, and asthma remains poorly controlled in many of these patients. This study assessed the rate of adherence to home nebulizer treatment in paediatric patients in China. Methods: The CARE study was a 12-week, multicentre, prospective, observational study across 12 tertiary hospitals in China. Patients were aged 0–14 years, clinically diagnosed with asthma and prescribed home nebulizer inhaled corticosteroid (ICS) therapy for ⩾3 months. The primary endpoint was electronically monitored treatment adherence. Patients attended onsite visits at 0, 4, 8 and 12 weeks to assess asthma control, severity and treatment adherence (recorded by electronic monitoring devices and caregivers). Results: The full analysis set included 510 patients. Median treatment adherence reported by electronic monitoring devices was 69.9%, and median caregiver-reported adherence was 77.9%. The proportion of patients with well-controlled asthma increased from 12.0% at baseline to 77.5% at visit 4. Increased time between asthma diagnosis and study enrolment was a significant predictor for better adherence [coefficient: 0.01, p = 0.0138; 95% confidence interval (CI): 0.00, 0.01] and asthma control (odds ratio = 1.001, p = 0.0498; 95% CI: 1.000, 1.002). Negative attitude to treatment by the caregiver was associated with poorer asthma control. Conclusions: Adherence to home nebulization, a widely used treatment for asthma, was high among Chinese pediatric patients. Asthma control improved with increasing treatment duration. These results suggest that home nebulization of ICS is an effective and recommendable long-term treatment for paediatric patients with asthma. Trial registration ClinicalTrials.gov identifier: NCT03156998 The reviews of this paper are available via the supplemental material section.